Mental and spiritual resilience of families based on the philosophy and local wisdom of the Mapur community - Kathryn, Susanna; Chandra, Donny Charles (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
This research examines the Mapur community in Bangka, exploring how their philosophy, local wisdom, and cultural traditions enhance their mental and spiritual resilience in the face of social, economic, and environmental changes brought about by modernization and natural resource exploitation. A qualitative case study approach was employed. Data were collected through in-depth interviews with key figures, including traditional leader Abok Gedoi, Suli, and community member Apriyatno. Participatory observation and focus group discussions (FGD) provided a collective perspective on cultural and spiritual practices. Thematic analysis was applied to identify core themes related to resilience. The findings highlight that the Mapur people rely on harmony with nature, cooperation, gender equality, and culture-based education to build mental and spiritual resilience. Traditions such as Nujuh Jerami and the Bukaladang system are crucial in fostering social cohesion and community solidarity. The study focuses on a single community, which limits the generalizability of its findings to broader populations. The study suggests practical intervention strategies, including integrating cultural values into resilience-building programs to enhance the well-being of the Mapur community. This research addresses a gap in the literature regarding the resilience of the Mapur people. It offers insights into the interplay between cultural traditions and mental and spiritual well-being, contributing to broader discussions on community resilience in indigenous populations.